Analisis Dan Perancangan Data Mart Kredit Pada Bank DKI - Munawar, Munawar; Irawan, Alfa Punky (Lembaga Penerbitan Universitas Esa Unggul, 2008)
Data warehouse/ data mart can support query in decision making.Building data warehouse/ data mart can give companies a strategic advantage over their competition. This advantage can come from several sources: the ability to access enterprise-wide data, the ability to have consistent data, and the ability to perform analysis quickly. Bank DKI intends to build data mart to help them make decision. Bank DKI can use the information in a datamart to spot trends in loan analysis, collection,Ã‚Â and its relationship. Once Bank DKI builds a data mart, chairman of this bank have a consistent surce for enterprise-wide data that allows for fast answers to query. Buidling data mart for loan usually means rearranging the loan data and performing data mining to look for trends that were previously unknown. Data mart help loan analys better understand individual clients and see widespread trends.Keywords: Analysis, Bank DKI, Loan, Data Mart, OLAP, Design